Fetal Aberrant Right Subclavian Artery: Associated Anomalies, Genetic Etiology, and Postnatal Outcomes in a Retrospective Cohort Study - Cai, Meiying; Lin, Na; Fan, Xiangqun; Chen, Xuemei; Xu, Shiyi; Fu, Xianguo; Xu, Liangpu; Huang, Hailong (Frontiers in Pediatrics, 2022)
Background: Aberrant right subclavian artery (ARSA) is becoming increasingly common in fetuses. However, there are relatively fewer studies regarding the genetic etiology of ARSA. We performed genetic analysis of fetuses with ARSA and followed up the pregnancy outcomes to evaluate the prognosis of the fetuses, providing information for prenatal and eugenic consultations. Methods: This retrospective study included 112 pregnant females whose fetuses were diagnosed with ARSA from December 2016 to February 2021. Fetal karyotype analysis and single-nucleotide polymorphism (SNP) array were performed. Results: The 112 fetuses were divided into two groups: the isolated ARSA group (n=48, 42.9%) and the non-isolated ARSA group (ARSA with other ultrasound abnormalities, n=64, 57.1%). The total rate of pathogenic copy number variation (CNV) observed using karyotype analysis (3/8) and SNP array (5/8) was 7.1% (8/112). The rates of pathogenic CNV in the isolated and non-isolated ARSA groups were 4.2% (2/48) and 9.4% (6/64), respectively. No significant difference was observed between the two groups (P=0.463). The results of genetic analysis influenced the parents' decision to terminate the pregnancy. During the follow-up examination, fetuses with ARSA without pathogenic CNV were found to have normal growth and development after birth. Conclusions: Fetuses with isolated ARSA have a low probability of being diagnosed with pathogenic CNV. However, when ARSA is complicated with other ultrasound abnormalities, the risk of pathogenic CNV remarkably increases. Prenatal genetic counseling and SNP-array should be recommended for better assessment of fetal prognosis.